Analysis and implementation of aquatic locomotion on robotic manta ray - Santoso, Ade Hartawan Johan. (2010)
To accommodate the environmental problem caused by propeller, alternative underwater propulsion system has been well researched. The development of efficient, maneuverable and yet eco-friendly propulsion method is greatly inspired by locomotion of fishes. There are two classification of fish locomotion based on the fins which is utilized to produce thrust. First, the body and caudal fin locomotion infers to group of fishes such as eels, tunas, and dolphins. They undulate or oscillate their body and caudal fin in order to create thrust. Second, the median and paired fin locomotion refers to fishes which use their pectoral fins, pelvic fins, dorsal fin or anal fin to swim. Stingrays, skates and sunfish are categorized under this group. Each type of locomotion has its own distinct features which give more advantage in swimming than any other locomotion.